Mechanotransduction and Biomechanical Properties of Bone Tissue as a Basis for the Use of Intraosseous Osteopathic Techniques - Valeryevich, Novoseltsev Svyatoslav; Germanovich, Reshetnikov Alexey; Dmitrievich, Vyunov Vladislav; Rasimovich, Suleymanov Timur; Maksimovna, Nefedova Anastasia; Grigorievich, Solomatov Petr (International Journal of Membrane Science and Technology, 2023)
The development and maintenance of bone mass is critical to movement, health, and quality of life. Bone mass is regulated by various factors, activation of biologically active substances, enzymes, including changes in mechanical load. The osteocyte network provides a wide-ranging load monitoring "network" that penetrates every cubic millimeter of bone tissue. Deformities or trauma create a limitation that can cause asymmetric bone growth, such as plagiocephaly. A deep understanding of the cellular mechanisms responsible for bone remodeling as well as bone mechanotransduction is essential for the development of effective exercise, osteopathic techniques, and pharmaceutical strategies to increase and/or prevent bone loss. This review summarizes current data on the main molecular mechanisms involved in bone mechanotransduction, which provides insight into bone tissue, methods of working with it, and points of application for correcting various dysfunctions to promote bone growth in length. This process is carried out by increasing the proliferation of chondrocytes and the activity of growth plates. This contributes to the correction of such consequences of intraosseous dysfunctions as the development of anatomical differences in the size of the lower extremities in children.